Tenure security research: Key findings and lessons learned - McLain, Rebecca (International Food Policy Research Institute, 2021)
Tenure insecurity has a variety of negative consequences for natural resource management, agricultural productivity, and poverty reduction, but the sources of tenure insecurity differ for men and women, and for individual, household, and collective lands. Research supported through PIM has helped advance policy reforms that improve access to, and tenure security of, land and natural resources and has supported more equitable and sustainable use of resources in less developed regions. Statutory recognition of customary rights, multistakeholder processes such as for land use planning, and organized social alliances such as Indigenous Peoples’ groups have emerged as important mechanisms for securing rights or enhancing access to collectively held lands. Long-term partnerships, ongoing engagement, and training for multiple actors at multiple scales increases the likelihood of successful implementation of tenure reforms. Further research on tenure security can contribute to achieving the Sustainable Development Goals, especially by clarifying how customary tenure can provide security and how tenure affects decision-making in multistakeholder platforms.